Combining discussion tools and inductive instruction to teach software engineering principles - Moura, Isabel Cristina A. A. (2011)
This research explores the effect on students’ achievements of combining the use of a forum tool and inductive instruction (i.e., project and other forms of active learning) in a Software Engineering (SE) introductory course. Using two different editions of the course, the study portrays the changes in it from the absence (in the 2008 edition) to the presence (in the 2009 edition) of directives to use an online forum for reusing students’ contributions “as resource for further learning”. About 80 undergraduates participated in the study. Data sources included students’ practices, individual and team contributions to the forum, and perceptions of using the discussion tool to learn SE principles. Although students tended mostly to read rather than post entries to the forum, this exploratory study shows how the above referred combination had a positive influence on students’ achievements, making them rise. Implications for the classroom and study drawbacks are discussed.